THE ROLE OF MILITARISM IN THE POLITICAL AND SOCIAL DYNAMICS OF MYANMAR SOCIETY - Hakiki, Ach (International Review of Humanities Studies, 2023)
This paper discusses how the Myanmar military took back power from the government, the democratic efforts built by the Myanmar government returned to a dream after the coup on 1 February 2021. The conflict between civil society and militarism became something that could not be avoided, people took to the streets and made a ceasefire, thousands of civilians were killed in the democracy they aspired to, some-ASEAN communities condemned the conflict that occurred. The purpose of this paper, to see how the dynamics of the Myanmar state in building a complete democracy with a military coup, as well as the role of the Military in the socio-political dynamics in Myanmar, the methodology used is a qualitative method, with the approach of conflict theory, welfare theory.